Psychic suffering of university nurses in the context of academic life - Deivson Wendell da Costa Lima; Jaciara Sampaio Gonçalves; Lívia Dayane Sousa Azevedo; Alcivan Nunes Vieira; Rosane Pilot Pessa; Margarita Antonia Villar Luis (Universidade Federal de Santa Maria, 2021)
Objective: to analyze the psychic suffering among nursing students in the context of academic life. Method: descriptive research, with a qualitative approach, carried out with 20 university students from the last semester of nursing, from a public university in the Northeast, Brazil. The data were produced by open-ended questions, between March 2016 and February 2017, and evaluated by content analysis. Results: the reasons for psychological suffering were the difficulties of adapting the university students at the beginning of the course, conflicts during training and expectations regarding the end of graduation. Given this, the consequences identified were dietary difficulties, stress and symptoms of depression. The way of life of university students is influenced by academic experiences, including eating habits, overwork and lack of leisure. They can be precursors of serious health problems, such as suicidal ideation. Conclusion: it is suggested to expand prevention and clinical management strategies at the university linked to mental health services.